MicroRNA-2187 Modulates the NF-κB and IRF3 Pathway in Teleost Fish by Targeting TRAF6 - Gao, Wenya; Chang, Renjie; Sun, Yuena; Xu, Tianjun (Frontiers in Immunology, 2021)
The innate immune organs and cells detect the invasion of pathogenic microorganisms, which trigger the innate immune response. A proper immune response can protect the organisms from pathogen invasion. However, excessive immunity can destroy immune homeostasis, leading to uncontrolled inflammation or pathogen transmission. Evidence shows that the miRNA-mediated immune regulatory network in mammals has had a significant impact, but the antibacterial and antiviral responses involved in miRNAs need to be further studied in lower vertebrates. Here, we report that miR-2187 as a negative regulator playing a critical role in the antiviral and antibacterial response of miiuy croaker. We find that pathogens such as Vibrio anguillarum and Siniperca chuatsi rhabdovirus (SCRV) can up-regulate the expression of miR-2187. Elevated miR-2187 is capable of reducing the production of inflammatory factors and antiviral genes by targeting TRAF6, thereby avoiding excessive inflammatory response. Furthermore, we proved that miR-2187 modulates innate immunity through TRAF6-mediated NF-κB and IRF3 signaling pathways. The above results indicate that miR-2187 acts as an immune inhibitor involved in host antibacterial and antiviral responses, thus enriching the immune regulatory network of the interaction between host and pathogen in lower vertebrates.